The effectiveness of the Buteyko breathing technique on clinical parameters in pediatric Asthma patients at the regional general hospital: A pilot study - Widyaningrum, Rahmah; Lentini, Zulyandra Dida; Emha, Maulida Rahmawati (Yayasan Pendidikan Kardin Assidiq, 2025)
Background: Asthma is a chronic non-communicable disease that significantly affects the pediatric population. Severe exacerbations can disrupt daily activities, increase morbidity, and even lead to mortality. Effective management of asthma requires a combination of pharmacological and non-pharmacological interventions. The Buteyko Breathing Technique (BBT) is a non-pharmacological therapy designed to reduce the frequency of asthma attacks and improve breathing patterns. Purpose: This study aimed to evaluate the effectiveness of the Buteyko breathing technique on clinical parameters, specifically respiratory rate and oxygen saturation, in pediatric asthma patients at Panembahan Senopati Regional General Hospital. Methods: This quantitative study employed a pre-experimental design using a one-group pretest–posttest approach. A sample of 11 pediatric patients, aged 5 to 18 years, was selected through convenience sampling. The inclusion criteria included children who were hospitalized for a minimum of three days, received bronchodilator therapy, and were willing to participate in the study. Clinical parameters, such as oxygen saturation and respiratory rate, were measured before and after the intervention using pulse oximetry and manual counting. Data were analyzed using the Wilcoxon signed-rank test. Results: The analysis revealed that the Buteyko breathing technique significantly reduced respiratory rates on the first day of the intervention (p < 0.001). However, there was no significant effect of the intervention on oxygen saturation levels (p > 0.05). Conclusion and recommendation: The Buteyko breathing technique is effective in reducing respiratory rates in pediatric asthma patients; however, it did not significantly alter oxygen saturation in this pilot study. It can be recommended as a complementary non-pharmacological management approach in conjunction with standard bronchodilator therapy. Further research with a larger sample size and a control group is needed to validate these findings.